2022
DOI: 10.1002/jdn.10234
|View full text |Cite
|
Sign up to set email alerts
|

Indole‐3‐carbinol ameliorated the neurodevelopmental deficits in neonatal anoxic injury in rats

Abstract: Neonatal anoxia is linked to long‐lasting neurodevelopmental deficits. Due to the lack of pharmacological intervention to treat neonatal anoxia, there is interest in finding new molecules for its treatment. Indole‐3‐carbinol (I3C) has shown neuroprotective effects in some disease conditions. However, the neuroprotective role of I3C in neonatal anoxia has not been explored. Consequently, we have investigated the effect of I3C on neonatal anoxia‐induced brain injury and neurodevelopmental deficits. Rat pups afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…I3C oral treatment has significantly ameliorated the neurodevelopment deficits in neonatal rats exposed to anoxia. The amelioration of neurodevelopment deficits could be due to the mitigation of hypoxia‐inducible factor‐1α (HIF‐1α), oxidative stress, mitochondrial dysfunction, and apoptosis (Ramakrishna & Krishnamurthy, 2022b). Hence, the above research findings indicate that I3C could be a promising neuroprotective agent in adult as well as neonatal stroke conditions.…”
Section: Cruciferous Phytochemicals and Their Neuroprotective Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…I3C oral treatment has significantly ameliorated the neurodevelopment deficits in neonatal rats exposed to anoxia. The amelioration of neurodevelopment deficits could be due to the mitigation of hypoxia‐inducible factor‐1α (HIF‐1α), oxidative stress, mitochondrial dysfunction, and apoptosis (Ramakrishna & Krishnamurthy, 2022b). Hence, the above research findings indicate that I3C could be a promising neuroprotective agent in adult as well as neonatal stroke conditions.…”
Section: Cruciferous Phytochemicals and Their Neuroprotective Activitiesmentioning
confidence: 99%
“…In vivo studies showed that KPF reduced rear reaction and freezing response by inhibiting the FAAH enzyme suggesting that KPF exhibits anxiolysis (Ahmad et al, 2020; Gupta et al, 2018). Cerebral palsy due to perinatal anoxia restricts the growth in neonates and causes motor dysfunctions (Ramakrishna & Krishnamurthy, 2023). KPF treatment for rat pups that underwent perinatal anoxia/cerebral palsy substantially increased body development, including body weight and body length.…”
Section: Cruciferous Phytochemicals and Their Neuroprotective Activitiesmentioning
confidence: 99%